TVET Outreach for Orang Asli spreads benefits of higher education - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 31 March 2022 - Over 300 Orang Asli of various ages attended the TVET Outreach Programme for Orang Asli@Lipis located in the Dewan Orang Ramai Pos Betau and Balai Raya Kampung Tementong Lipis.